Physical Location of New PCR-Based Markers and Powdery Mildew Resistance Gene(s) on Rye (Secale cereale L.) Chromosome 4 Using 4R Dissection Lines - Duan, Qiong; Wang, Yang Yang; Qiu, Ling; Ren, Tian Heng; Li, Zhi; Fu, Shu Lan; Tang, Zong Xiang (Frontiers in Plant Science, 2017)
Rye (Secale cereale L.) 4R chromosome contains elite genes that are applicable for application in wheat (Triticum aestivum L.) cultivar improvement. PCR-based 4R-specific markers can facilitate benefit the detection of elite genes on 4R in wheat backgrounds. In this study, a new fluorescence in situ hybridization (FISH) map of the 4RKu chromosome of Kustro rye Kustro has been built. A set of 4RKu dissection lines were was obtained and 301 new 4RKu-specific markers were developed using sSpecific lLength aAmplified fFragment sSequencing (SLAF-seq) technology. The 301se markers were combined with the 99 4RKu-specific markers previously developed, and by us previously were physically mapped to 4RKu chromosome using the new FISH map of 4RKu chromosome and the 4RKu dissection lines. A total of 338 of the 400 markers have been successfully mapped to six regions of 4RKu chromosome. In additionAdditionally, the powdery mildew resistance gene(s) on the 4RLKu arm has beenwas located to the segment between L.4 and L.8, and the same region where the 115 4RLKu-specific markers were mapped. The markers developed in this study can be used to identify a given specific segment of 4R chromatin in wheat backgrounds, to help to construct a high-density physical map of 4R chromosome, and to facilitateaccelerate the utilization of elite genes on 4R chromosome in wheat breeding programs.